A rechargeable molecular solar thermal system below 0 °C. Issue 23 (26th May 2022) - Shangguan, Zhichun; Sun, Wenjin; Zhang, Zhao-Yang; Fang, Dong; Wang, Zhihang; Wu, Si; Deng, Chao; Huang, Xianhui; He, Yixin; Wang, Ruzhu; Li, Tingxian; Moth-Poulsen, Kasper; et al.
Abstract : We demonstrate rationally designed arylazopyrazoles as MOST-PCM that can be circularly charged and discharged below 0 °C with visible light. Abstract : An optimal temperature is crucial for a broad range of applications, from chemical transformations, electronics, and human comfort, to energy production and our whole planet. Photochemical molecular thermal energy storage systems coupled with phase change behavior (MOST-PCMs) offer unique opportunities to capture energy and regulate temperature. Here, we demonstrate how a series of visible-light-responsive azopyrazoles couple MOST and PCMs to provide energy capture and release below 0 °C. The system is charged by blue light at −1 °C, and discharges energy in the form of heat under green light irradiation. High energy density (0.25 MJ kg −1 ) is realized through co-harvesting visible-light energy and thermal energy from the environment through phase transitions. Coatings on glass with photo-controlled transparency are prepared as a demonstration of thermal regulation. The temperature difference between the coatings and the ice cold surroundings is up to 22.7 °C during the discharging process. This study illustrates molecular design principles that pave the way for MOST-PCMs that can store natural sunlight energy and ambient heat over a wide temperature range.